Homologous overexpression of hydrogenase and glycerol dehydrogenase in Clostridium pasteurianum to enhance hydrogen production from crude glycerol. (July 2019) - Sarma, Shyamali; Ortega, David; Minton, Nigel P.; Dubey, Vikash Kumar; Moholkar, Vijayanand S.
Graphical abstract: Highlights: Genetic engineering of C. pasteurianum for glycerol bioconversion. Overexpression of hydrogenase ( hydA ) increased the hydrogen yield by 1.7 fold. Overexpression of dhaD1 and dhaK enhanced glycerol uptake and H2 yield by 1.5 fold. Higher hydrogen yield was associated with higher specific enzyme activities. Acetate and 1, 3-PDO are the major byproducts of glycerol bioconversion. Abstract: This study reports engineering of a hypertransformable variant of C. pasteurianum for bioconversion of glycerol into hydrogen (H2 ). A functional glycerol-triggered hydrogen pathway was engineered based on two approaches: (1) increasing product yield by overexpression of immediate enzyme catalyzing H2 production, (2) increasing substrate uptake by overexpression of enzymes involved in glycerol utilization. The first strategy aimed at overexpression of hydA gene encoding hydrogenase, and the second one, through combination of overexpression of dhaD1 and dhaK genes encoding glycerol dehydrogenase and dihydroxyacetone kinase. These genetic manipulations resulted in two recombinant strains ( hydA ++ / dhaD1K ++ ) capable of producing 97% H2 (v/v), with yields of 1.1 mol H2 /mol glycerol in hydA overexpressed strain, and 0.93 mol H2 /mol glycerol in dhaD1K overexpressed strain, which was 1.5 fold higher than wild type. Among two strains, dhaD1K ++ consumed more glycerol than hydA ++ which proves that overexpression of glycerol enzymes has enhanced glycerol intake rate.